Consumers’ Preferences for Accelerating the Circular Economy Transition in Taiwan: Evidence from a Discrete Choice Experiment - Arockia E J Ferdin; Matthew Lee Inman; Jia Wei Chook; Liyana Binti Yamin; Tashi Tshering Lham (Circular Economy and Sustainability, 2026)

From Linear to Circular: Consumer Perspectives on Breaking Free from Single-Use Plastics in Taiwan - Arockia E J Ferdin; Matthew Lee Inman; Jia Wei Chook (Circular Economy and Sustainability, 2025)

Oceanic turbulence from a planktonic perspective - Peter J. S. Franks; Bryce G. Inman; Jennifer A. MacKinnon; Matthew H. Alford; Amy F. Waterhouse (Limnology and Oceanography, 2022)
The potential influences of turbulence on planktonic processes such as nutrient uptake, grazing, predation, infection, and mating have been explored in hundreds of laboratory and theoretical studies. However, the turbulence levels used may not represent those experienced by oceanic plankton, bringing into question their relevance for understanding planktonic dynamics in the ocean. Here, we take a data‐centric approach to understand the turbulence climate experienced by plankton in the ocean, analyzing over one million turbulence measurements acquired in the open ocean. Median dissipation rates in the upper 100 m were −8 W kg −1 , with 99% of the observations −6 W kg −1 . Below mixed layers, the median dissipation rate was ~ 10 −10 W kg −1 , with 99% of the observations −7 W kg −1 . Even in strongly mixing layers the median dissipation rates rarely reached 10 −5 W kg −1 , decreasing by orders of magnitude over 10 m or less in depth. Furthermore, episodes of intense turbulence were transient, transitioning to background levels within 10 min or less. We define three turbulence conditions in the ocean: weak ( −8 W kg −1 ), moderate (10 −8 –10 −6 W kg −1 ), and strong (> 10 −6 W kg −1 ). Even the strongest of these is much weaker than those used in most laboratory experiments. The most frequent turbulence levels found in this study are weak enough for most plankton—including small protists—to outswim them, and to allow chemical plumes and trails to persist for tens of minutes. Our analyses underscore the primary importance of planktonic behavior in driving individual interactions.

Assessing inundation damage and timing of adaptation: sea level rise and the complexities of land use in coastal communities - Brenda B. Lin; Yong Bing Khoo; Matthew Inman; Chi-Hsiang Wang; Sorada Tapsuwan; Xiaoming Wang (Mitigation and Adaptation Strategies for Global Change, 2014)

Risk Management in the Pharmaceutical Product Development Process - Matthew H. Hulbert; Liam C. Feely; Eugene L. Inman; Alton D. Johnson; Albert S. Kearney; James Michaels; Michael Mitchell; Elena Zour (Journal of Pharmaceutical Innovation, 2008)